2009
DOI: 10.1089/jamp.2008.0722
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Equipment Hygiene: A Belgian National Survey

Abstract: The Belgian CF Association sent this questionnaire to all Belgian CF patients. Of the 903 questionnaires distributed, 379 (42%) were returned. Fifty-two, 40 and 8% of patients used a vibrating-mesh nebulizer, jet nebulizer, or ultrasonic device, respectively. Ninety-eight percent of patients cleaned their material and soap was used by 35% of patients. Disinfection was performed by 91% of the patients and was daily performed by 57% of patients. Thermal disinfection (boiling water or sterilizer), a hypochlorite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This baseline measure of current practice revealed that a high proportion of adult CF patients (50%) and 20% of paediatric carers never disinfect their nebuliser, with none of the adults disinfecting it daily and only 42% of parents of children with CF doing so. These findings concur with a national study in Belgium, which reported that although the majority of patients cleaned their nebulisers on a daily basis, only 57% performed disinfection daily (Reychler et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…This baseline measure of current practice revealed that a high proportion of adult CF patients (50%) and 20% of paediatric carers never disinfect their nebuliser, with none of the adults disinfecting it daily and only 42% of parents of children with CF doing so. These findings concur with a national study in Belgium, which reported that although the majority of patients cleaned their nebulisers on a daily basis, only 57% performed disinfection daily (Reychler et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, in CF decreased adherence has been shown to correlate with poorer lung health, therefore a fast reliable method of cleaning is extremely important to this patient cohort [15]. A Belgian study found that only 57% of patients cleaned home inhalation devices daily as recommended [16]. A rapid and easy disinfection method would potentially improve adherence to daily disinfection and be consistent with other proposed strategies to reduce the treatment burden [17].…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that although patients are familiar with the importance of nebuliser care, often, the mesh component is never cleaned nor is an appropriate method of disinfection chosen, which in turn will have damaging effects on the mesh [ 5 , 7 ]. Decreased nebuliser output, increased nebulisation duration and nebulisers prematurely switching off have been reported in a number of studies examining e-Flow Rapid nebuliser evaluation delivering tobramycin over a 6-month period [ 7 , 8 ].…”
Section: Why Is There a Need To Clean And Disinfect Nebulisers?mentioning
confidence: 99%
“…It has been reported that although patients are familiar with the importance of nebuliser care, often, the mesh component is never cleaned nor is an appropriate method of disinfection chosen, which in turn will have damaging effects on the mesh [ 5 , 7 ]. Decreased nebuliser output, increased nebulisation duration and nebulisers prematurely switching off have been reported in a number of studies examining e-Flow Rapid nebuliser evaluation delivering tobramycin over a 6-month period [ 7 , 8 ]. Due to the fact that the manufacturer's MeshCare system, which involves a reverse rinse of the nebuliser mesh with isotonic saline (5 mL for 20 min) by means of a bespoke small shower head significantly improves nebuliser performance, it is advised to use this system on a monthly basis and particularly when the duration of nebulisation time is increased [ 8 ].…”
Section: Why Is There a Need To Clean And Disinfect Nebulisers?mentioning
confidence: 99%
See 1 more Smart Citation